Ageist attitudes are already evident in pre‐ and early‐school children: A multi‐method examination. - Jaquet, Jenny; Schenker, Lena‐Emilia; Bellingtier, Jennifer A.; Kornadt, Anna E.; Riediger, Michaela (British Journal of Developmental Psychology, 2025)
We examined age‐related attitudes in 56 German children (Mage = 6.5, 4–8 years; 55% female) using newly developed behavioural (seating and team formation task), explicit (picture rating) and implicit [single‐target implicit association test (ST‐IAT)] measures. Stimuli comprised pictures of younger and older adults. Children placed younger adults closer to themselves and placed more older adults in an opposing team, rated pictures of younger adults more positively than those of older adults, and evinced more favourable implicit evaluations of younger than older targets. This shows that already young children evaluate younger and older adults differently, underscoring the need for further research on the development of age‐related attitudes in childhood.